2015
DOI: 10.1371/journal.pone.0143059
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Responsiveness to Hypercapnia Is Stable over Six Months in Older Adults

Abstract: The primary purpose of this Brain in Motion (BIM) sub-study was to determine the 6-month stability of resting blood flow velocity and cerebrovascular responsiveness to a euoxic hypercapnic challenge in a group of physically inactive community dwelling men and men aged ≥55 yrs (range 55–92 yrs). At baseline and 6 months later 88 women (65±6 yr) and 78 men (67±7 yr) completed a hypercapnic challenge (step changes from resting end-tidal PCO2 ((PETCO2) to +1, +5 and +8 mmHg above rest) while cerebral blood flow ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…The responsiveness of the cerebrovasculature to changing CO 2 levels appears to be maintained during acute posture changes (Tymko et al 2015) and stable over time (Spencer et al 2015). However, it has not been investigated during or after exposure to a chronic headward fluid shift, nor J Physiol 598.12 after exposure to a chronic hypercapnic environment.…”
Section: Cerebrovascular Reactivitymentioning
confidence: 99%
“…The responsiveness of the cerebrovasculature to changing CO 2 levels appears to be maintained during acute posture changes (Tymko et al 2015) and stable over time (Spencer et al 2015). However, it has not been investigated during or after exposure to a chronic headward fluid shift, nor J Physiol 598.12 after exposure to a chronic hypercapnic environment.…”
Section: Cerebrovascular Reactivitymentioning
confidence: 99%
“…First, the lack of a control group in the study precludes the ability to make firm conclusions on the exclusive role of the aerobic exercise intervention in improving cardiovascular and cerebrovascular indices. However, we have previously published data on lack of changes in cerebrovascular outcomes in the 6 months preceding the intervention (Spencer et al, 2015). These previous findings strengthened the role of the intervention in the improvements observed in this report.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study by Spencer et al. () assessed the stability of resting cerebral blood flow and cerebrovascular reactivity over 6 months in a similar cohort of older adults as the one used in this study. They demonstrated that peak middle cerebral artery velocity and reactivity were stable over a 6‐month period when normalized to PnormalETCO2.…”
Section: Discussionmentioning
confidence: 99%